THE FORMALISATION OF ISLAMIC ATTIRE IN PADANG, WEST SUMATRA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2009)
This study examines the formalisation of Islamic attire among Minangkabau people – particularly among school students in Padang, West Sumatra – in the spirit of the regional autonomy of post-Soeharto Indonesia. It focuses on the conceptualisation and enforcement of the Mayor’s policy concerning Islamic attire for students in the Mayoral Decree (No. 451.422/2005) in line with the rampant Shari>`ah-influenced by-laws throughout West Sumatra. I argue that the formalisation of Islamic attire has been unproductive in terms of promoting Islamic precepts because veiling is an ever-contested concept within the complex Muslim social structure. The imposition of this ‘contested concept’ has led to veiling becoming an ‘imposed choice’ that has assumed a formal meaning as proper religious attire for the wearer. Instead of enhancing religious awareness, the imposition of Islamic attire on students in public schools has failed to encourage a personal awareness of religious and cultural identity in them.